Design a hybrid solar/wind power converter - Koh, Wee Yong. (2012)
Renewable energy is a growing sector of the energy generation market in the world today. The U.S. Energy Information Administration predicts renewable energy will make up 17 percent of total electrical generation by 2035. Renewable energy comprises wind, hydropower, biofuels and solar energy.